Biopolymers in Drug and Gene Delivery Systems (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue focuses on fundamental and applied aspects of the design, characterization, and properties of biopolymeric drug and gene delivery systems. It contains eleven articles, including nine original research papers and two reviews. The papers cover various topics related to the use of biopolymers (polysaccharides such as cellulose and its derivatives, starch and its derivatives, chitosan and its derivatives, hyaluronan, sodium alginate, agarose, arabinoxylan, heparin, cyclodextrin, peptides and proteins, and synthetic biopolymers) for delivery of various drugs and therapeutic nucleic acids. The biomaterials studied include polymer conjugates, nano- and submicroparticles, gels, films, and implants for drug administration via intravascular, intravitreal, buccal, topical, and implantation routes.